Assessment of Development Potential for Central Government Irrigation Zones in Metro City - Pratama, Muhammad Vareza; Purwadi, Ofik Taufik; Romdania, Yuda; Zakaria, Ahmad; Herison, Ahmad (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2025)
The decline in agriculture, forestry, and fisheries sector revenue by 5.24% in Metro City in 2024 necessitates efforts to increase productivity through the development of irrigation areas (D.I). This study aims to analyze the existing conditions of central authority irrigation areas and assess their expansion potential according to the 2013 KP-01 standards. The research employs a mixed-method approach, utilizing quantitative analysis for spatial data processing and planning criteria assessment, complemented by qualitative analysis for interpretation and deepening of results. The findings indicate that the Karangrejo and Tejo Agung Clusters meet all eight criteria of the KP-01 irrigation planning standards, with an increase in irrigated land area from 18.71 hectares to 388.62 hectares. Both clusters demonstrate moderate soil fertility with adequate water sources from the Way Bunut River and reservoir for Karangrejo, and the Batanghari River with D.I. Way Sekampung channel for Tejo Agung. The analysis also confirms the fulfillment of aspects including water availability, farmer presence, road access, land ownership status, flood resistance, and compliance with Metro City's spatial planning (RTRW). In conclusion, the development of irrigation areas in both clusters is feasible and should be implemented through a planned and integrated approach to enhance agricultural productivity and water management effectiveness in Metro City.